2021
DOI: 10.1038/s41598-021-90912-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water level in vertical aquaculture systems on production performance, biochemistry, hematology, and histology of Anguilla bicolor bicolor

Abstract: The water level in the cultivation of eel (Anguilla bicolor bicolor) is an important study in order to provide the optimal water level for cultivation. Optimizing the water level will affect the substitution of respiration energy with energy to grow. In addition, the water level information is related to the efficiency of water use for eel production in the future. Information on water level for eel production is still very limited, so this research is necessary to do. A total of 120 eel elver (initial weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Previous studies showed that air exposure can destroy the histological structures of many tissues, including gill, skin, intestines, and hepatopancreas, in aquatic animals (Lu et al, 2021;Harianto et al, 2022). In the current study, we observed the histopathological alterations of the hepatopancreas in C. fluminea under air exposure.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies showed that air exposure can destroy the histological structures of many tissues, including gill, skin, intestines, and hepatopancreas, in aquatic animals (Lu et al, 2021;Harianto et al, 2022). In the current study, we observed the histopathological alterations of the hepatopancreas in C. fluminea under air exposure.…”
Section: Discussionsupporting
confidence: 59%
“…When exposed to air, aquatic animals have less access to oxygen and face severe stress of hypoxia. Lots of evidence indicate that severe air exposure will cause several adverse effects on aquatic animals, such as oxidative stress injury, cell apoptosis, destruction of the histological structure, disruption of energy homeostasis, poor muscle quality, reduced growth, and even death (Arlinghaus and Hallermann, 2007;Gu et al, 2017;Lu et al, 2021;Harianto et al, 2022). To cope with desiccation and hypoxia stress of air exposure, aquatic animals can mobilize multiple adaptive physiological and molecular mechanisms, including changing respiratory metabolic strategies, enhancing immune function, increasing antioxidant defense, and altering gene expression (Romero et al, 2007;Bao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This result is higher when compared to other studies, namely eels reared in aquaponics systems, phytoremediation in large volumes of water with growth and feed conversion values of 0.3%-1.19% and 1.57-3.91 respectively [16,35]. Other studies have shown that the lower water level used in elver eel research in vertical aquaculture results in high specific growth rates and low FCR [36]. Other results in this study indicate that the lower the water needs, the better the difference between final and initial weights, AWG and FC.…”
Section: Production Performancementioning
confidence: 74%
“…Blood glucose describes the physiological response of fish to environmental changes. High blood glucose values indicate a stress response in fish (Harianto et al 2021). The lowest blood glucose was observed on day 45 th of treatment B about 20 mg dL -1 , while the highest blood glucose was observed on day 60 th of treatment C (53 mg dL -1 ).…”
Section: Discussionmentioning
confidence: 93%